Root development in Leucaena leucocephala (Lam.) de Wit enhances copper accumulation - Bomfim, Nayane Cristina Pires [UNESP]; Aguilar, Jailson Vieira [UNESP]; Ferreira, Tassia Caroline [UNESP]; dos Santos, Beatriz Silvério [UNESP]; de Paiva, Wesller da Silva [UNESP]; de Souza, Lucas Anjos; Camargos, Liliane Santos [UNESP] (Springer Nature, 2023)
Potentially toxic elements (PTE) in soil like copper (Cu) have been common in agricultural and mining areas worldwide. The sustainable remediation of these areas has been shown to have high socio-environmental relevance and phytoremediation is one of the green technologies to be considered. The challenge is to identify species that are tolerant to PTE, and to assess their phytoremediation potential. The objective of this study was to evaluate the physiological response of Leucaena leucocephala (Lam.) de Wit and to determine the species tolerance and phytoremediation potential to concentrations of Cu in the soil (100, 200, 300, 400 and 500 mg/dm3). The photosynthetic rate was not affected, while the content of chlorophylls decreased as Cu concentrations increased. There was an increased in stomatal conductance and water use efficiency from the treatment of 300. The root biomass and the length were bigger than the shoots, in the treatments above 300. Cu accumulation was greater in the roots than in the shoot of the plants, thus, the Cu translocation index to the shoot was lower. The ability to absorb and accumulate, mainly, Cu in the roots, allowed the development and growth of plants, since the parameters of photosynthesis and biomass accumulation were not affected by the Cu excess. This accumulation in the roots is characterized as a strategy for the phytostabilization of Cu. Therefore, L. leucocephala is tolerant to the Cu concentrations evaluated and has a potential phytoremediation of Cu in the soil.
Keywords: Biomass; Excess copper; Photosynthetic pigments; Phytoremediation; Phytostabilization; Potentially toxic elements; Tolerance index; Trace element